Encountering the Dain: Space-Time, Witchcraft Anxiety, and Gaddi Tribal Belonging - Simpson, Nikita (HIMALAYA - The Journal of the Association for Nepal and Himalayan Studies, 2023)
Outwardly, most Gaddi people refute the relevance and danger of witchcraft in present times. At another level, however, rumors of jadu (witchcraft, or spells and curses performed by a witch) and opara (black magic, or curses that may be performed by anyone) circulate in particular places, caste neighborhoods, and households. This article argues that the study of the discourses of witchcraft—anxieties, rumors, suspected afflictions—provides a window into the changing shape of tribal belonging in the Gaddi community. Drawing on the theory of witchcraft developed by Nancy Munn (1986), the article suggests that witchcraft is an intersubjective practice that generates and manipulates space-time. In the Gaddi case, this manifests in a temporal split. On the one hand, Gaddi people eschew their reputation for witchcraft, rooted in British colonial stereotypes, to break from stigmatizing and marginalizing assumptions about their religious and social practices as they strive for tribal dignity. On the other, the persistent rumors of witchcraft within the Gaddi community articulate a struggle over the contours and values of tribal belonging as it is bound with caste distinction, class mobility, and gendered generational change. Focusing on the complexities of the Gaddi case, this article suggests that witchcraft—when understood through a politics of space-time—remains a valuable tool for South Asian anthropologists as they investigate the nexus of tribe, caste, and class relations.